The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/tri.13131
|View full text |Cite
|
Sign up to set email alerts
|

Liver graft-to-spleen volume ratio as a useful predictive factor of the early graft function in children and young adults transplanted for biliary atresia: a retrospective study

Abstract: A graft volume/standard liver volume ratio (GV/SLV) > 35% or graft/recipient weight ratio (GRWR) > 0.8% has been considered as a standard criteria of graft selection. Even if the graft size meets these selection criteria, small-for-size syndrome can still occur depending on the portal venous flow (PVF). The aim of this study was to identify other factors contributing to portal hyperperfusion and the post-transplant course, focusing on the graft volume-to-spleen volume ratio (GV/SV). Thirty-seven BA patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Sanefuji et al reported that SFSS occurred in patients with GV/SLV <40% and this finding has been confirmed by others. 2,28 Ikegami et al also found no association between SFSS and GV/SLV or GRWR and these authors highlighted the issue of over predicting GV. 30 The authors found that actual graft volume was significantly lower than expected.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Sanefuji et al reported that SFSS occurred in patients with GV/SLV <40% and this finding has been confirmed by others. 2,28 Ikegami et al also found no association between SFSS and GV/SLV or GRWR and these authors highlighted the issue of over predicting GV. 30 The authors found that actual graft volume was significantly lower than expected.…”
Section: Discussionmentioning
confidence: 97%
“…17 Interestingly, two studies found that splenic volume was a better predictor of SFSS than GV/SLV and GRWR. 28,33 Osman et al showed that PVP >15 mmHg and GRWR <0.8 in combination more reliably predicts SFSS (OR 10.0, p = 0.001). 19 Studies have focused on the upper limit of PVP and most have aimed for either PVP <15 mmHg or PVP <20 mmHg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that graft-to-spleen-volume-ratio (GSVR) may guide decision on the need for PIM. [145][146][147][148][149] Gyoten et al reported that GSVR <0.95 predicts PVP of >20 mm Hg. 150 Cheng et al reported a GSVR of <0.60 was highly associated with post-transplant elevated PVF.…”
Section: Indications For Pim In Sfsgmentioning
confidence: 99%
“…Recipients with a final portal vein pressure (PVP) ≤ 15 mmHg or a pressure gradient of PVP-central vein pressure (CVP) ≤ 5 mmHg have a better prognosis[ 43 ]. In another study, liver-graft-to-spleen-volume ratio was used to predict early graft function in children and young adults undergoing LDLT, in which < 0.88 predicted portal hyperperfusion[ 44 ]. Moreover, a MELD score > 20[ 45 ], a decline in the platelet (PLT) count at post operation day (POD) 3 > 56%[ 46 ] and donor age > 45 years are also risk factors for a poor prognosis in recipients of small-for-size grafts[ 19 ].…”
Section: Small-for-size Grafts In Ldltmentioning
confidence: 99%